PHYTOCHEMICAL SCREENING AND ANTIMYCOBACTERIAL POTENTIALS OF Syzygium guineense WILD DC. AND Mimosa pigra LINN (2014)
The prevalence of multi-drug resistant tuberculosis is an increasing health challenge. Attention has therefore been shifted to the use of ethno-medicines in combating this disease. Traditionally, Syzygium guineense (stem-bark) and Mimosa pigra (aerial parts) are used in the treatment of respiratory tract infections with no scientific justification. This study was designed to identify the constituents of Syzygium guineense and Mimosa pigra that may be active against Mycobacterium tuberculosis. The S. guineense (stem-bark) and M. pigra (aerial parts) were obtained from farmlands in Abuja and authenticated at the herbarium of National Institute for Pharmaceutical Research and Development, Abuja. The S. guineense (1.0 kg) was extracted successively with chloroform and methanol. The extracts were separately fractionated with n-hexane followed by acetone. Mimosa pigra (0.5 kg) was extracted with methanol and partitioned with diethylether and n-butanol. The fractions were purified using chromatographic techniques. The extracts, fractions and isolated compounds were subjected to antimycobacterial assay with Mycobacterium tuberculosis (ZMC 050 and 303) strains using the Lowenstein-Jensen and mycobacterium growth indicator tube methods. Streptomycin, isoniazid, rifampicin, and ethambutol were used as standard drugs and dimethylsulphoxide as negative control. The structures of the isolated compounds were elucidated using infrared, ultra-violet/visible, nuclear magnetic resonance and mass spectroscopic techniques. The chloroform extract of S. guineense yielded 4.1 g n-hexane fraction and 5.2 g acetone fraction A while the methanol extract gave 5.2 g acetone fraction B and 98.0 g residue. Crude methanol extract of M. pigra gave 40.1, 4.6 and 12.3 g of diethylether, n-butanol and residue fractions respectively. Two new triterpenoids were isolated from S. guineense namely: 12-hydroxy-27-demethylfriedelan-3-one and betulinic acid methylenediol ester, in addition to the two known triterpenoids: betulinic acid, and friedelan-3-one. One new flavonoid, 8-hydroxy-3-phenyl-4-benzopyrone rhamnoside was isolated from M. pigra. The two plants‘ methanol extracts, n-butanol fraction, acetone fraction A, and isolated compounds: betulinic acid, betulinic acid methylenediol ester and 8-hydroxy-3-phenyl-4- benzopyrone rhamnoside were active against ZMC 050 strain with Minimum Inhibitory Concentrations (MIC) of 5.0, 5.0, 2.0, 0.6, 0.6, 0.15 and 0.5 mg/mL respectively. The ZMC 303 strain also gave similar MIC values as ZMC 050 strain. Spectroscopic analysis of 12-hydroxy-27-demethylfriedelan-3-one provided evidence for δH signals: 0.8-1.2 UNIVERSITY OF IBADAN LIBRARY iv (7CH3), 1.2-1.8 (10CH2), and 2.2-2.4 (5CH), δC signals: 29.9-41.7 (5C), 72.8 (1CHOH) and 213.4 (1C=O) with a molecular ion of 428 corresponding to C29H48O2. The betulinic acid methylenediol ester showed δH and δC signals similar to betulinic acid except for the downfield methylenedioxy carbinol (OCH2O) δC signal at 79.0 and molecular ion of 486 correspond to C31H50O4. Betulinic acid and friedelan-3-one signals are similar to published spectra. The 8-hydroxy-3-phenyl-4-benzopyrone rhamnoside showed δH signals: 0.9 (3Hd, J=5.8 Hz), 3.1-3.8 (overlapping glycone multiplet) and 5.2 (anomeric) typical of a rhamnose moiety, with δH 6.2 (1H), 6.4 (1H), 6.9 (5H) and δC 178.0 (1C=O) of the flavonoid ring. The bioactive compounds obtained from Syzygium guineense and Mimosa pigra exhibited anti-mycobacterial activities. They have potentials for the development of drugs for the management of tuberculosis. The new triterpenoids and flavonoids are addition to the library of compounds. Keywords: Syzygium guineense, Mimosa pigra, Antimycobacterial activity, Triterpenoids Word count: 484